PELATIHAN KEWIRAUSAHAAN UNTUK MENGEMBANGKAN KREATIFITAS DAN MINAT BERWIRAUSAHA BIDANG PERTANIAN - Puspita, Popi; Labo, Den Syahrudin; Lesmana, Dedi (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2021)
Argamakmur is located in one of the highlands that supports agricultural locations. One way to overcome this is through entrepreneurship, therefore by having an interest in entrepreneurship it will encourage new job opportunities to reduce unemployment and create prosperity in the city of Argamakmur. Growing interest in entrepreneurship for students at SMKN 2 Argamakmur is an alternative to reducing unemployment. It is hoped that students will be able to identify from an early age creative business ideas that can be realized as preparation for becoming young entrepreneurs. The service carried out to the community in this activity took the form of training and FGD (Focus Group Discussion) and it can be concluded that the counseling and demonstration went smoothly without any obstacles, the community was able to understand how to maintain business strategies. The positive response shown by the students can be seen during the training which was attended by all students at SMK 2 Argamakmur.